2018
DOI: 10.1097/md.0000000000010672
|View full text |Cite
|
Sign up to set email alerts
|

Association between VEGF genetic variants and diabetic foot ulcer in Chinese Han population

Abstract: The aim of this study was to investigate the association of vascular endothelial growth factor (VEGF) gene polymorphisms with diabetic foot ulcer (DFU) susceptibility in a Chinese Han population.Around 88 type 2 diabetes mellitus (T2DM) patients without DFU and 97 T2DM patients with DFU were enrolled in this study. A total of 103 age and gender matched healthy individuals were recruited as healthy control. VEGF gene polymorphisms rs699947 and rs13207351 were analyzed by polymerase chain reaction restriction fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 30 publications
2
22
0
2
Order By: Relevance
“…In addition, one genome-wide association study conducted by Meng et al 33 , which included 699 diabetic foot ulcers and 2695 controls, indicated that the single-nucleotide polymorphism rs80028505 of MAPK14 was a risk factor for diabetic foot ulcers. Another study aimed to investigate the relationship between VEGF gene polymorphisms and DFCs in a Chinese population showed that the VEGF gene could be a susceptible gene of DFCs 36 . Another study found that polymorphisms in cytokine/chemokine genes had a close association with amputation and severe infection in individuals with DFCs 38 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, one genome-wide association study conducted by Meng et al 33 , which included 699 diabetic foot ulcers and 2695 controls, indicated that the single-nucleotide polymorphism rs80028505 of MAPK14 was a risk factor for diabetic foot ulcers. Another study aimed to investigate the relationship between VEGF gene polymorphisms and DFCs in a Chinese population showed that the VEGF gene could be a susceptible gene of DFCs 36 . Another study found that polymorphisms in cytokine/chemokine genes had a close association with amputation and severe infection in individuals with DFCs 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Genetic and ethnic factors play an important role in not only DPN but also DFCs 32 . Several studies have identified that some genetic variants may be potential risk factors for DFCs, such as the polymorphisms of MAPK14 33 , TNFRSF11B 34 , MCP1 35 , VEGF 36 , 37 , TNF-α 38 , and osteoprotegerin gene 39 . In addition, one genome-wide association study conducted by Meng et al 33 , which included 699 diabetic foot ulcers and 2695 controls, indicated that the single‐nucleotide polymorphism rs80028505 of MAPK14 was a risk factor for diabetic foot ulcers.…”
Section: Discussionmentioning
confidence: 99%
“…The VEGFA factor can strengthen neoangiogenesis under those conditions and maintain the blood vessels homeostasis [48] , VEGFA may also mediate the response of increases in permeability and angiogenesis, especially in brain [49] . In the endothelial cells, VEGFA can facilitating cellular migration and sprouting [50] , and also have some roles in cancer pathology, inflammation and wound healing [51,52] .…”
Section: Discussionmentioning
confidence: 99%
“…These polymorphisms were found to be associated with DFU formation and progression (Li et al, 2018). In addition, a significant association was found between the VEGF polymorphism (rs699947) and DFU In an Iraqi study that investigated the molecular basis of the SNP (rs699947) and its correlation with biochemical parameters, such as glycated hemoglobin (HbA1c) and glutathione (GSH).…”
Section: Types Of Polymorphisms Associated With Dfumentioning
confidence: 99%